THE IMPORTANCE OF ENGLISH IN TODAY’S WORLD - Eshmirzayeva, Nozima Bahodir qizi (Educational Research in Universal Sciences, 2023)
This article discusses the importance of English in today’s world. English has become one of the most widely spoken languages in the world, serving as a common language for communication, business, education, and diplomacy. The importance of English cannot be overstated as it provides a gateway to global opportunities, facilitating cross-cultural communication and promoting cultural exchange.